Food losses and Waste at Bakeries, Retail and Household Levels –A Case of Sweden : a Case of Sweden - Balasooriya, Balasooriya Mudiyanselage Indrachapa Dhananjani (SLU/Department of Molecular Sciences, 2022)
Reducing food waste is necessary to assure food security and overcome environmental issues. This study was aimed to assess food losses and waste (FLW) along bakery, retail, food service and household stages of bread value chain in Sweden, causes and identify potential measures to reduce losses and waste. Both quantitative and qualitative analyses were carried out. Both primary and secondary data were used in the study. The FLW was 80450tonnes per year in the entire Swedish bread supply chain. Household contributed to the highest waste fraction (37.2%) of bread waste in entire value chain among the bakery, retail, restaurant and canteen stages followed by the retail (34.9%), bakery (14.9%) and restaurants (8.9%), Canteens (3.3%). The major causes of FLW in household were forgetting to consume after purchase and over purchase of bread. Th most frequent cause for bread waste in bakeries were over production, TBA and poor production planning. Overstocking and passing expiry dates were identified as the most frequent causes of bread waste at retails and food services. More causes such as lack of knowledge regarding the issue, lack of attention, lack of collaborative effort among the actors, demand-driven food system, consumer demands for more types of bread products, etc. were identified. Strategies and actions identified to reduce waste and losses were proper sales and order planning, increasing awareness of FLW, reducing over purchase, freeze storage after purchase, prepare different products from left-over bread which have more shelf life, serve only sufficient amounts at food services, prepare different recipes at restaurants and canteens to motivate the consumers to finish what is served, donate to feed people in need and for animal feed, recycle food rather than wasting.